Vildagliptin-Metformin: Is it a causative of cardiac muscle failure in Type 2 Diabetic patients? - YRKM Sai (International Journal of Clinical Endocrinology and Metabolism - Peertechz Publications, 2021)
Vildagliptin is an oral anti-hyperglycaemic agent, commonly called an anti-diabetic medication that belongs to the family of medications known as Dipeptidyl Peptidase-4 (DPP-4) inhibitors. It is a medicine that is used to treat Type 2 Diabetes Mellitus [1].